2022
DOI: 10.1097/upj.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Diversity among U.S. Urology Residency Programs and Efforts to Improve It: You Can’t Be What You Can’t See

Abstract: Introduction: The U.S. urology workforce lacks ethnic and gender diversity. Few programs exist to increase diversity, and little is known on their effectiveness. We assessed the landscape of specific programs designed to increase underrepresented in medicine (URiM) and female student participation in the U.S. Urology Match, and understand the concerns and attitudes of those students.Methods: To better understand urology-specific programs, we sent an 11-item survey to all 143 urology residency programs. To bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…15 Adding to these dynamics, a survey of urology residents from various programs found that the vast majority were unaware of any institution-specific programs geared toward supporting URiM or female students. 16 Addressing these issues and creating an inclusive culture within residency programs are crucial for attracting and retaining a diverse group of urologists.…”
Section: Discussionmentioning
confidence: 99%
“…15 Adding to these dynamics, a survey of urology residents from various programs found that the vast majority were unaware of any institution-specific programs geared toward supporting URiM or female students. 16 Addressing these issues and creating an inclusive culture within residency programs are crucial for attracting and retaining a diverse group of urologists.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, programs with any URiM and female faculty have better success at recruiting such candidates. 5 However, there is a persistent underrepresentation of female urology faculty members, a percentage that diminishes when looking at women in urology department leadership positions. 3 There is a parallel scarcity of URiM urology faculty members.…”
mentioning
confidence: 99%
“…There have been improved Match rates among participants compared to the general pool of URiM urology applicants. 5…”
mentioning
confidence: 99%